Knowledge, attitudes, and practices related to breast cancer screening among female health care professionals: a cross sectional study - Heena, Humariya (BMC Womens Health, 2019)
BACKGROUND: Incidence of breast cancer in the Kingdom of Saudi Arabia (KSA) has increased in recent years. Screening helps in early detection of cancer and early diagnosis and timely treatment of breast cancer lead to a better prognosis. Women in the healthcare profession can have a positive impact on the attitudes, beliefs, and practices of general public. Therefore, it is important that the healthcare workers themselves have adequate knowledge and positive attitudes. We conducted a study to assess the knowledge, attitudes, and practices related to breast cancer screening among female healthcare professionals. METHODS: A cross-sectional study was conducted on female health professional of KFMC (King Fahad Medical City). Data was collected using a pre-designed, tested, self-administered questionnaire. The questionnaire included specific sections to test the participants’ knowledge, attitude, and practices related to cervical cancer and its screening. Data analysis was done using descriptive statistics. RESULTS: A total of 395 health care workers participated in this study. The mean age of the participants was 34.7 years. Participants included physicians (n = 63, 16.0%), nurses (n = 261, 66.1%), and allied health workers (n = 71, 18.0%). Only 6 (1.5%) participants had a good level of knowledge of breast cancer and 104 (26.8%) participants demonstrated a fair level of knowledge. Overall, 370 (93.7%), 339 (85.8%), and 368 (93.2%) participants had heard of breast self-examination, clinical breast examination, and mammography, respectively. A total of 295 (74.7%) participants reported practicing breast self-examination, 95 (24.1%) had undergone clinical breast examination, and 74 (18.7%) had ever undergone mammography. CONCLUSION: The knowledge, attitudes, and practices related to breast cancer screening were found to be lower than expected. Active steps are required to develop educational programs for the health care staff, which might empower them to spread the knowledge and positively influence the attitudes of female patients in the hospital.